TARIK ULUR KEBEBASAN PERS DI DALAM RUANG PERSIDANGAN (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2023)
The covering of the trial in court by the mass media raises pros and cons, even raising allegations of an attempt to weaken press freedom. This research tries to find out the dynamics of regulation of press freedom in the trial and the importance of it. In order to answer these problems, the authors conducted research using normative juridical research methods. The results of this study indicate that regulations related to media coverage in trials are often changed by the government or by the court. It has been noted that the statutory regulations governing this matter have been amended several times. On the other hand, there is an important reason why the press needs freedom to report on disputes, namely because the press institution is the fourth pillar of democracy, one of which is social control (the media as a watchdog). Keywords: press freedom, trial coverage regulation, court.